Disrupting and design thinking education : new technology, designs, and business models - Meadows, C. J. (Carolyn Jean) (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2025)
"Meadows proposes an approach to the education business that begins with needs, and proposes educational and business models, supported by new technologies. This book takes a design-thinking and disruption perspective on the future of education. Beginning with shocking statistics on cost, time, and lengthy debt repayment, it presents a clear case for disruption in the education sector. It continues by examining future skills in the age of AI, machine learning, and robotics. In this new age, businesses need a new kind of workforce, and workers need to equip themselves to survive and thrive. Drawing upon tools and techniques from disruption and design-thinking, Meadows puts forward new frameworks of education, business, and technology -- all with examples of educators (and learners) already doing it today. This book provides rigorous thinking and practical guidance for professionals in the education industry and budding education entrepreneurs, as well as homeschooling parents"--
"Routledge Focus" -- from cover.
Keywords: Educational planning; Education -- Effect of technological innovations on; Business and education; Education -- Economic aspects; Labor supply -- Effect of education on; EDUCATION / Teaching Methods & Materials / General; BUSINESS & ECONOMICS / Entrepreneurship; EDUCATION / Home Schooling